Advertising and Pr-Technologies Influence on Creation and Promotion Russian and Spanish Regions Image as Tourist Destinations - Burnyasheva, Ludmila; Goncharova, Oksana; Korneevets, Valentin (Anais Brasileiros de Estudos Turísticos, 2022)
The article considers the current, previously unaffected in scientific research, problem of the influence of advertising and PR technologies on the creation and promotion of the image of Russian and Spanish regions as tourist destinations. A strategy is being developed and proposed to increase the rating of tourist destinations of Spanish and Russian resorts based on the introduction of advertising and PR technologies. The author notes that at present there is an increasing need for effective advertising of tourist organizations, which need to regulate the impact on the state of public opinion of target audiences. For this reason, the increasing importance of the information and communication component of the activities of tourist destinations is being updated. The high importance of the image of tourist destination for the successful promotion of the region stimulates the study of this topic, the research of existing experience. As a result, the author studies the practice of applying advertising and PR technologies in the formation of the region’s image, determines its effectiveness. It is further concluded that, in the modern information age, the quantity and quality of information in the World Wide Web largely depends on the development of tourism in specific regions and countries. It is also emphasized that it is necessary to monitor the development of events in order to respond in time to changing situations.